Breed-dependent associations of production characteristics with on-farm seropositivity for Ostertagia ostertagi in dairy cows - Lisa Kuehne; Martina Hoedemaker; Christina Strube; Gabriela Knubben-Schweizer; Andrea Springer; Andreas W. Oehm (Parasites & Vectors)
Abstract Background Pasture-borne parasites like Ostertagia ostertagi have a negative effect on dairy cow health and productivity. The aim of the present study was to assess potential breed-dependent associations of O. ostertagi seropositivity with dairy cow production traits, i.e. milk yield, milk fat and milk protein. Methods We describe these associations in German Holstein (GH) cows, a specialised dairy breed, compared with a dual-purpose breed, i.e. German Simmental (SIM). Data from 560 farms across Germany housing 93,030 dairy cows were included. Of the 560 farms, 383 farms housed GH cows and 177 housed SIM. Potential breed-dependent associations of O. ostertagi seropositivity with production characteristics were explored via a two-way interaction term using quantile regression. Pasture access, farming type (organic vs. conventional), herd size (number of cows) and study year were included as confounders. The relationship of O. ostertagi seropositivity with production traits based on breed was further examined via estimated marginal means. Results Ostertagia ostertagi bulk tank milk (BTM) seropositivity was associated with lower median milk yield, milk fat and milk protein on GH farms, whereas no differences could be detected between seropositive and seronegative SIM farms. The difference in the production parameters per cow and year at GH farms associated with O. ostertagi seropositivity were 631.6 kg milk yield (P < 0.001), 20.0 kg milk fat (P < 0.001) and 17.0 kg milk protein (P = 0.01). Conclusions This study indicated differential associations of O. ostertagi seropositivity and production level of cows depending on breed. Our results suggest that seropositivity is associated with lower milk yield, milk fat and milk protein in high-performance dairy breeds, whereas no such association may be present in dual-purpose breeds. Graphical Abstract